Injection of ligand-free gold and silver nanoparticles into murine embryos does not impact pre-implantation development - Taylor, Ulrike; Garrels, Wiebke; Barchanski, Annette; Peterson, Svea; Sajti, Laszlo; Lucas-Hahn, Andrea; Gamrad, Lisa; Baulain, Ulrich; Klein, Sabine; Kues, Wilfried A.; Barcikowski, Stephan; Rath, Detlef (Beilstein Journal of Nanotechnology, 2014)
Intended exposure to gold and silver nanoparticles has increased exponentially over the last decade and will continue to rise due to their use in biomedical applications. In particular, reprotoxicological aspects of these particles still need to be addressed so that the potential impacts of this development on human health can be reliably estimated. Therefore, in this study the toxicity of gold and silver nanoparticles on mammalian preimplantation development was assessed by injecting nanoparticles into one blastomere of murine 2 cell-embryos, while the sister blastomere served as an internal control. After treatment, embryos were cultured and embryo development up to the blastocyst stage was assessed. Development rates did not differ between microinjected and control groups (gold nanoparticles: 67.3%, silver nanoparticles: 61.5%, sham: 66.2%, handling control: 79.4%). Real-time PCR analysis of six developmentally important genes (BAX, BCL2L2, TP53, OCT4, NANOG, DNMT3A) did not reveal an influence on gene expression in blastocysts. Contrary to silver nanoparticles, exposure to comparable Ag+-ion concentrations resulted in an immediate arrest of embryo development. In conclusion, the results do not indicate any detrimental effect of colloidal gold or silver nanoparticles on the development of murine embryos.
Keywords: biomedical application; confocal microscopy; gene expression; protein corona; toxicity